Neurodevelopmental difficulties negatively affect health-related quality of life in children with idiopathic clubfoot - Lööf, E.; Andriesse, H.; Broström, E.; André, M.; Böhm, S.; Bölte, Sven (Wiley-Blackwell Publishing Ltd., 2019)
Aim: To study health-related quality of life (HRQoL) in children with idiopathic clubfoot (IC) and the influence of sex, clubfoot laterality and neurodevelopmental difficulties (NDD) on HRQoL. Methods: A cross-sectional questionnaire-based study in Stockholm and Skåne Counties, Sweden, of 106 children with IC born 2004–2007 (mean 9.4 ± 0.6 years) and a general population sample of 109 schoolchildren (mean 9.5 ± 0.6 years). The children and their caregivers answered the EQ-5D-Y (Youth) and Five to Fifteen questionnaires to operationalise HRQoL and NDD, respectively. Results: No reduced HRQoL on the EQ-5D-Y dimensions were reported by 51% of the children with IC, and 71% in the general population sample, with significant more problems in the IC sample regarding ‘mobility’, ‘doing usual activities’ and ‘having pain or discomfort’, despite similar overall health status. Neither sex nor clubfoot laterality affected HRQoL. Children with IC and NDD combined reported more problems in three out of five dimensions and lower overall health status compared with children with IC alone. Conclusion: Despite similar overall health status, children with IC had more HRQoL problems compared with the general population, being associated with coexisting NDD but not sex or clubfoot laterality.